LA DIMENSIÓN DIALÓGICA EN LA REFUTACIÓN DE LA DONACIÓN DE CONSTANTINO DE LORENZO VALLA. - Vilar, Mariano (Talia Dixit, 2025)
This article analyzes Lorenzo Valla's De falso credita et ementita Constantini donatione based on its connections to the dialogue genre, which he cultivated in works such as De vero bono, De libero arbitrio, and De professione religiosorum. Although structured as a forensic oratio, the text incorporates resources from the humanistic disputatio--prosopopoeia, apostrophe, enargeia, concessio--that turn it into a "dialogue in absentia" with historical and imaginary adversaries. The study shows how Valla constructs plausible scenes to highlight the implausibility of the Constitutum Constantini, personifies figures such as the forger "Palea" to expose their ignorance or hypocrisy, and employs concessio as a dialectical trap that reinforces his refutation. These strategies serve not only a stylistic function but also shape a "dialogical critique" in which philology becomes performative, revives the past, and strips texts and institutions of their authority. It is concluded that this work combines forensic rhetoric and dialogical dramatization to transform philological criticism into an act of intellectual emancipation, affirming the primacy of reason and evidence over all hierarchy.